2012
DOI: 10.1128/mcb.06754-11
|View full text |Cite
|
Sign up to set email alerts
|

Kinase Suppressor of Ras 2 (KSR2) Regulates Tumor Cell Transformation via AMPK

Abstract: Kinase suppressor of Ras 1 (KSR1) and KSR2 are scaffolds that promote extracellular signal-regulated kinase (ERK) signaling but have dramatically different physiological functions. KSR2 ؊/؊ mice show marked deficits in energy expenditure that cause obesity. In contrast, KSR1 disruption has inconsequential effects on development but dramatically suppresses tumor formation by activated Ras. We examined the role of KSR2 in the generation and maintenance of the transformed phenotype in KSR1 (28,55,57). In C. eleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 63 publications
0
59
0
Order By: Relevance
“…MIN6 cells have been used in earlier studies for measurements of cellular bioenergetics [46,47], which indicated that these cells are an appropriate model for these experiments. Our studies indicated that MIN6 β-cells in which ENT3 had been knocked down by transient transfection with siRNAs exhibited significantly higher levels of basal respiration, which was caused both by enhanced ATP-linked respiration and increased proton leak.…”
Section: Discussionmentioning
confidence: 99%
“…MIN6 cells have been used in earlier studies for measurements of cellular bioenergetics [46,47], which indicated that these cells are an appropriate model for these experiments. Our studies indicated that MIN6 β-cells in which ENT3 had been knocked down by transient transfection with siRNAs exhibited significantly higher levels of basal respiration, which was caused both by enhanced ATP-linked respiration and increased proton leak.…”
Section: Discussionmentioning
confidence: 99%
“…Ras V12 -activated AMPK␣1/␣2 null MEFs are resistant to tumor formation in vivo, with increased susceptibility to anoikis (36,37), and KSR2-dependent MEF transformation requires AMPK activation (38). AMPK activity is increased in early stages of gliomas (39).…”
Section: Discussionmentioning
confidence: 99%
“…The shRNA for Rap1a, Rap1b, B-Raf, and C-Raf were described previously (13,16,(63)(64)(65)(66). The sense KSR1 shRNA oligonucleotide is GTGC-CAGAAGAGCATGATA (human sequence, corresponding to the mouse KSR1 siRNA) (67).…”
Section: Methodsmentioning
confidence: 99%